1998
DOI: 10.1074/jbc.273.1.215
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Phosphorylation Sites in Hormone-sensitive Lipase That Are Phosphorylated in Response to Isoproterenol and Govern Activation Properties in Vitro

Abstract: Hormone-sensitive lipase (HSL) is the rate-limiting enzyme in lipolysis. Stimulation of rat adipocytes with isoproterenol results in phosphorylation of HSL and a 50-fold increase in the rate of lipolysis. In this study, we used site-directed mutagenesis and two-dimensional phosphopeptide mapping to show that phosphorylation sites other than the previously identified Ser-563 are phosphorylated in HSL in response to isoproterenol stimulation of 32 P-labeled rat adipocytes. Phosphorylation of HSL in adipocytes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
336
4
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 422 publications
(367 citation statements)
references
References 33 publications
16
336
4
6
Order By: Relevance
“…1). Although it was known for several years that PKA increased HSL activity through a phosphorylation-dependent mechanism, mutagenesis experiments demonstrated dependence for this effect on phosphorylation at Ser 563 , Ser 659 , and Ser 660 (2,67). However, it should be noted that there is some doubt as to the importance of Ser 563 (2).…”
Section: Regulation Of Tg Lipasesmentioning
confidence: 91%
See 1 more Smart Citation
“…1). Although it was known for several years that PKA increased HSL activity through a phosphorylation-dependent mechanism, mutagenesis experiments demonstrated dependence for this effect on phosphorylation at Ser 563 , Ser 659 , and Ser 660 (2,67). However, it should be noted that there is some doubt as to the importance of Ser 563 (2).…”
Section: Regulation Of Tg Lipasesmentioning
confidence: 91%
“…Although it was known for several years that PKA increased HSL activity through a phosphorylation-dependent mechanism, mutagenesis experiments demonstrated dependence for this effect on phosphorylation at Ser 563 , Ser 659 , and Ser 660 (2,67). However, it should be noted that there is some doubt as to the importance of Ser 563 (2). The PKA phosphorylation of HSL results in modest activation of the enzyme (2-to 3-fold) and promotes the translocation of HSL to the LD (21), an effect that is critical for enhancing lipolytic capacity as a result of ␤-adrenergic stimulation.…”
Section: Regulation Of Tg Lipasesmentioning
confidence: 99%
“…These modulations require an increase in the transcription factor steroid regulatory element-binding protein (SREBP)-1c [55]. In adipocytes, insulin also inhibits lipolysis through inhibition of the enzyme hormone-sensitive lipase (HSL) [56]. Recent data showed that protein kinase B (PKB) is required for the regulation of lipogenesis and for the antilipolysis effect of insulin [57].…”
Section: Insulin Molecular Signalling Pathwaysmentioning
confidence: 99%
“…However, studies performed on a purified preparation of the catalytic subunit of PKA revealed dose-dependent inhibition by vanadium [36]. The decrease of isoprenaline-induced PKA activation observed in response to vanadate and a low concentration of pV would presumably lead to a lowering of PKA-mediated phosphorylation and activation of hormone-sensitive lipase [37] that could explain the anti-lipolytic effect of these agents. However, a direct effect of these agents on hormone-sensitive lipase also cannot be excluded.…”
Section: Discussionmentioning
confidence: 98%